Can grip strength be used as a surrogate marker to monitor recovery from shoulder fatigue?. (August 2018) - Hawkes, David; Grant, Michael; McMahon, Jessica; Horsley, Ian; Khaiyat, Omid
Abstract: Muscular fatigue impacts on normal shoulder function, which is particularly pertinent to throwing athletes. This study aimed to investigate the relationship between grip strength and shoulder muscle fatigue to evaluate the role of grip strength as a surrogate measure for upper limb performance. Twenty healthy participants were recruited. EMG was recorded from 15 shoulder muscles during different fatiguing contractions: an initial baseline recording (Fat-Baseline); after a shoulder exhausting exercise regime (Fat-Exhaustion); and after a 10 min rest period (Fat-Recovery). Grip strength was similarly measured in the same conditions. Grip strength differed significantly across the testing scenarios (p = 0.012–<0.001). Greater fatigue was seen in anterior deltoid, middle deltoid, posterior deltoid and supraspinatus in the Fat-Exhaustion contraction as compared to the Fat-Baseline contraction (p = <0.001–0.043). Greater fatigue was seen during the Fat-Recovery contraction for the trapezius, serratus anterior and biceps brachii as compared to the Fat-Exhaustion contraction (p = 0.008–0.038). Grip strength decreased following an exhausting exercise protocol but recovered to baseline following a rest period. Conversely, EMG indices of fatigue did not recover. Additional fatigue was seen reflecting a reorganisation of movement strategy. Therefore, susceptibility to injury still exists if grip strength alone is used as a barometer of upper limb performance.